Blood disorders typically associated with renal transplantation - Yang, Yu; Yu, Bo; Chen, Yun (Frontiers in Cell and Developmental Biology, 2015)
Renal transplantation has become one of the most common surgical procedures performed to replace a diseased kidney with a healthy kidney from a donor. It can help patients with kidney failure live decades longer. However, renal transplantation also faces a risk of developing various blood disorders. The blood disorders typically associated with renal transplantation can be divided into two main categories: 1) Common disorders including post-transplant anemia (PTA), post-transplant lymphoproliferative disorder (PTLD), post-transplant erythrocytosis (PTE) and post-transplant cytopenias (PTC, leukopenia/neutropenia, thrombocytopenia and pancytopenia); and 2) Uncommon but serious disorders including hemophagocytic syndrome (HPS), thrombotic microangiopathy (TMA), therapy-related myelodysplasia (t-MDS), and therapy-related acute myeloid leukemia (t-AML). Although many etiological factors involve the development of post-transplant blood disorders, immunosuppressive agents and viral infections could be the two major contributors to most blood disorders and cause hematological abnormalities and immunodeficiency by suppressing hematopoietic function of bone marrow. Hematological abnormalities and immunodeficiency will result in severe clinical outcomes in renal transplant recipients. Understanding how blood disorders develop will help cure these life-threatening complications. A potential therapeutic strategy against post-transplant blood disorders should focus on tapering immunosuppression or replacing myelotoxic immunosuppressive drugs with lower toxic alternatives, recognizing and treating promptly the etiological virus, bacteria or protozoan, restoring both hematopoietic function of bone marrow and normal blood counts, and improving kidney graft survival.